Highly Enhanced Triboelectric Performance from Increased Dielectric Constant Induced by Ionic and Interfacial Polarization for Chitosan Based Multi‐Modal Sensing System. (6th November 2021) - Sun, Jingzhe; Choi, Hyeongsub; Cha, Seokjun; Ahn, Dahye; Choi, Minseok; Park, Sangki; Cho, Yujang; Lee, Jiwoo; Park, Tae‐eon; Park, Jong‐Jin
Abstract: The coexistence of increasingly severe environmental concerns and bio‐signal sensing systems drives the development of environmental affinity and energy harvesting materials. Chitosan is a richly sourced biodegradable material derived from crustaceans, which provides a new option for environmentally, wearable triboelectric nanogenerator (TENG). In this paper, the triboelectric performance of chitosan blends are proposed to enhance the dielectric constant by optimizing the ionic polarization and interface polarization for the first time, which fills in the blank of enhancing the output of chitosan triboelectric by systematically engineering in ionic/molecular and pH effect. Triboelectric output enhanced chitosan film in TENG shows an output voltage 3 times (18 V) higher than that of the initial film and 25 times (200 V) higher after corona charge injection. The chitosan film for wearable devices not only can be used as a unit of a triboelectric device to measure human motion signal, but also can be used as a piezoresistive sensor (Δ R / R 0 : 0 to 1.5) and an air humidity sensor (relative humidity: 20% to 90%) after mixing carbon black. The study provides a stimulating example that triboelectric nano generator/piezoresistive sensor is made from chitosan and used in the multi‐modal sensing system. Abstract : By adding ions and molecules and adjusting the pH, the dielectric constant of the chitosan film is enhanced through ionic and interfacial polarization. After corona charge injection, the output voltage of the optimized film can reach 25 times the initial value. Chitosan solution can be used to manufacture both triboelectric and piezoresistance devices, thus assembling the holistic healthcare sensing system.